Industrial work practice management to enhance students' industry-relevant competence - Edi Purwanto; Tina Rahmawati; Tarso Tarso; Hidayah Uswatun Kasanah (Universitas Pendidikan Indonesia, 2025)
Industrial Work Practice (Praktik Kerja Industri or Prakerin) is a crucial component of vocational education aimed at strengthening the link between the world of education and the world of work. This study aims to describe the management of Prakerin implementation at SMK Muhammadiyah 1 Sleman in enhancing the alignment of students' competencies with the demands of the business and industrial sectors. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the implementation of Prakerin is carried out through systematic stages of planning, organizing, implementation, and evaluation. The school has established partnerships with various industries, particularly official workshops such as Toyota and Daihatsu, to ensure the achievement of students' technical competencies. Student competencies are deemed in line with industry needs, particularly in technical skills and professional attitudes. Supporting factors for the implementation of Prakerin include the readiness of facilities, the quality of vocational teachers, and the school's network of industry partners. However, challenges remain, such as mismatches in internship placements, limited supervision in small-scale industries, and administrative obstacles. Therefore, strengthening partnerships, enhancing supervision, and improving the evaluation system are necessary to optimize and sustain the Prakerin program in bridging vocational education and the workforce. Abstrak Praktik Kerja Industri (Prakerin) merupakan komponen penting dalam pendidikan vokasi yang bertujuan untuk memperkuat keterkaitan antara dunia pendidikan dan dunia kerja. Penelitian ini bertujuan untuk mendeskripsikan manajemen pelaksanaan Praktik Kerja Industri (Prakerin) di SMK Muhammadiyah 1 Sleman dalam meningkatkan kesesuaian kompetensi peserta didik dengan tuntutan Dunia Usaha dan Dunia Industri. Menggunakan pendekatan kualitatif deskriptif, data diperoleh melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pelaksanaan Prakerin dilaksanakan melalui tahapan perencanaan, pengorganisasian, pelaksanaan, dan evaluasi secara sistematis. Sekolah menjalin kerja sama dengan berbagai industri, terutama bengkel resmi seperti Toyota dan Daihatsu, untuk memastikan ketercapaian kompetensi teknis peserta didik. Kompetensi peserta didik dinilai sesuai dengan kebutuhan DUDI, khususnya dalam aspek teknis dan sikap profesional. Faktor pendukung pelaksanaan Prakerin meliputi kesiapan sarana, kualitas guru produktif, dan jaringan mitra industri. Namun, masih dijumpai kendala seperti ketidaksesuaian tempat praktik, keterbatasan pengawasan di industri kecil, serta hambatan administratif. Oleh karena itu, penguatan kemitraan, peningkatan pendampingan, dan perbaikan sistem evaluasi dibutuhkan agar program Prakerin dapat berjalan lebih optimal dan berkelanjutan dalam menjembatani pendidikan vokasi dengan dunia kerja. Kata Kunci: dunia usaha dan industri; kompetensi peserta didik; manajemen prakerin